A comparative investigation of anionic polysaccharides (sulfated fucan, ι-carrageenan, κ-carrageenan, and alginate) on the fabrication, stability, rheology, and digestion of multilayer emulsion. (January 2023) - Shi, Feifei; Chang, Yaoguang; Shen, Jingjing; Chen, Guangning; Xue, Changhu
Abstract: In this study, four important marine polysaccharides (sulfated fucan, ι-carrageenan, κ- carrageenan, and alginate) were selected and tailored to a similar molecular weight using heterologously overexpressed enzymes. These "standardized" polysaccharides were firstly used to elucidate the effect of anionic polysaccharides on the formation, stability, rheology, and digestion of the multilayer emulsions. Results showed that the four polysaccharides were all capable of adsorbing to the surfaces of lipid droplets at the pH values of 5, 4, and 3. ι-Carrageenan could adsorb to the surface of the droplet at a higher pH (pH 6) than the other three polysaccharides (pH 5). Stable multilayer emulsions were formed at a higher polysaccharide concentration (0.05 wt%) for κ-carrageenan compared with sulfated fucan, ι-carrageenan, and alginate (0.04 wt%). The emulsion containing alginate was susceptible to flocculation at low pH (pH 3) and high polysaccharide concentration (>0.1 wt%). Multilayer emulsions fabricated by ι-carrageenan were stable under all the examined NaCl concentrations (0–400 mM). Multilayer emulsion fabricated by sulfated fucan showed less aggregation in the stomach stage, which is a good choice to encapsulate acid-intolerant substances. Multilayer emulsions fabricated by κ-carrageenan and alginate showed higher apparent viscosity, and the rheological curves of multilayer emulsions fabricated by FUC or ICA were quite similar. Moreover, multilayer emulsions fabricated by κ-carrageenan showed the fastest digestion rate and the highest digestion extent. These findings would facilitate the targeted design of multilayer emulsions by selecting suitable polysaccharides. Graphical abstract: Image 1 Highlights: Four polysaccharides were tailed to similar molar mass by a repertoire of enzymes. Multilayer emulsion with targeted functions was fabricated using polysaccharides. ι-Carrageenan can fabricate multilayer emulsion with high salt stability demand. κ-Carrageenan can form multilayer emulsion with the demand of rapid digestion. Emulsion contained sulfated fucan had less aggregation in the stomach stage.